Characteristics and in‐hospital outcomes of elderly patients with cancer in a top‐ranked hospital in China, 2016–2020: Real‐world study. (26th September 2022) - Huang, Lei; Shi, Yan; Wang, Lei; Rong, Lan; Ren, Yan; Xu, Chenying; Wu, Junwei; Zhang, Mingmin; Zhu, Lifeng; Zhang, Junjie; Xu, Xiaofeng; Hu, Weiguo; et al.
Abstract: Background: Cancer is mostly a disease of aging, and older patients with cancer are generally frailer. This study aimed to describe the characteristics and in‐hospital outcomes and explore factors associated with duration, cost, and mortality during first hospitalization, in older patients with cancer admitted to a top‐ranked hospital in China. Methods: Data on patients with solid cancer ≥65 years consecutively hospitalized in 2016–2020 were retrieved from the electronic medical records of Ruijin Hospital in Shanghai, China. Baseline characteristics, duration, cost, and mortality during hospitalization were described. Factors associated with duration, cost, and mortality during first hospitalization were explored using multivariable‐adjusted logistic regression. Results: 20, 650 eligible patients with male proportion of 59% and median age of 70 years were analyzed. 45% of the patients underwent resection in our hospital. Upon first admission, 49% of patients had hypertension, 19% diabetes, 22% weight loss, and 28% risks of malnutrition. The median duration and cost of first hospitalization were 9 days and 32, 000 RMB, respectively. 118 (0.6%) and 228 (1.1%) deaths occurred during first and any hospitalization, respectively. For first hospitalization, longer duration and higher cost were positively associated with older ages, male gender, emergency admission, certain tumor locations and histology, histories of diabetes, cirrhosis, and anticoagulant intake, higher body mass index, weight loss, reduced food intake, risk of falling, and worse self‐care ability; in‐hospital mortality was positively associated with age ≥85 years, emergency admission, certain cancer types, histories of hypertension and psychotropic intake, reduced food intake, and worse self‐care ability. Conclusions: This study identified certain baseline patient and tumor characteristics, medical and medication histories, changes of weight and food intake, diet, and self‐care ability which were independently associated with in‐hospital outcomes among older patients with cancer admitted to our hospital and which should be paid special attention to. While the factors might not be easily modifiable, our study can help identify patients at higher risks of inferior in‐hospital outcomes. Abstract : This real‐world study identified certain baseline patient and tumor characteristics, medical and medication histories, changes of weight and food intake, diet, and self‐care ability which were independently associated with in‐hospital outcomes among 20, 650 older patients (≥65 years) with cancer admitted to a top‐ranked hospital in China during 2016‐2020, and which should be paid special attention to. Our study can help to identify patients at higher risks of inferior in‐hospital outcomes.